EFFECT OF BIO FERTILIZERS ON GROWTH OF SOME TURFGRASS PLANTS - & Abdal-Latife, Sabry (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was conducted in the research fields, College of Agriculture, University of Baghdad, Al-Jadrya site during winter season (1/12/2015) to the end of summer season (31/8/2016) to investigate the influence of Bio-Fertilizers of four varieties of lawn grasses and their mixture on the growth of these grasses.The study included four varieties of lawn grasses one of them was from the warm season while the other three varieties were from cold season. Four mixture of those varieties were mixed in different percentage and eight treatments were prepared as follows: (T1) Bermuda grass (Cynodon dactylon), (T2) Kentucky blue grass (Poa pratensis), (T3) Long fescue grass (Festuca arundinacene), (T4) Ray grass (Lolium perennel), (T5) A mixture of Bermuda grass and Kentucky blue grass at 80:20, (T6) A mixture of Bermuda grass and Long fescue grass at 80:20, (T7) A mixture of Bermuda grass and Ray grass at 80:20, (T8) A mixture of Bermuda grass and Kintucky grass and Long fescue grass and Ray grass at 70:10:10:10. Two levels of Bio-Fertilizers were used. The first without Bio-Fertilizers (B0) and the second level was Bio-Fertilizers with a mixture of Azotobacter chroococcum and Azospirillum brasilin (B1).The vegetative, roots growth and visual characters were studied. The experiment was carried out using split plot design with 16 treatments in three replicates. Results were analyzed using Genstat, means were compared using L.S.D at 5% level of significance. Results showed a significant effect of plant type on the studied traits:The highest percentage of phosphor and potassium in Bermuda grass during summer season(0.36, 1.61%), the highest dry matter percentage in vegetative parts in summer seasons (43.79%), roots long (30.38cm), the nitrogen percentage(1.39%) and dry matter in the roots.The Long fescue grass showed a significant increase in the nitrogen at summer season (2.37%) and the percentage of potassium in winter season (2.17%). The Kentucky blue grass was characterized by high percentage of nitrogen, dry matter in winter season (1.68, 25.33%) and the degree of color winter season(8.26). The Bio-Fertilizers in all treatments significantly increased all the studied characters.